Religiosity Negotiation Among Migrant University Students in Urban Jakarta: A Qualitative Study - Salsabila Wulandari; Mushlihin Mushlihin; Suci Nurpratiwi (MASI Mandiri Edukasi, 2026)
Rapid urbanization generates structural social change and reshapes everyday lifestyles, creating new challenges for migrant students in sustaining religious commitment within metropolitan settings. This study examines how urban social dynamics shape migrant students' religiosity and explores how religious life is negotiated amid heterogeneous values and weakened social control. Using a qualitative descriptive design, data were collected through in-depth interviews and field observations with 16 migrant students from regions outside Jakarta who have resided for 3 to 4 years in boarding houses, dormitories, and rented residences in the Rawamangun area, East Jakarta. The findings reveal that adaptation to urban culture is a key factor shaping variations in religiosity. Some students adjust their religious practices to align with urban social expectations, resulting in reduced consistency of worship, while others maintain religious routines as a moral anchor and coping resource. Distinct psycho-spiritual patterns emerge between students who internalize urban lifestyles and those who preserve religious discipline, indicating that religiosity functions both as a vulnerable domain under urban pressure and as a source of resilience in navigating urban life.